Investigation of PIN Diode Characteristics for Wireless Communication Application - Sabri, Siti Nur Idayu; Sanudin, Rahmat (Evolution in Electrical and Electronic Engineering, 2021)
PIN diode is one of the key devices in wireless communication circuits that enable the RF wireless communication services to the users due to the difference in the characteristics of the PIN diode. The electrical properties, switching speed and power handling of PIN diodes for wireless communication applications are being investigated in this paper. Generally, a set of pre-determined controlled factors, which are specified by particular formulas, will impact the output properties of the PIN diode. The results suggest that the width of the PIN diode does play a crucial part as per functionality of the PIN diode, in which wider width of the PIN diode will result in lower resistance. It is concluded that there are several characteristics of PIN diode that should be considered to suit the application of wireless communication.